Directing cell delivery to murine atherosclerotic aortic lesions via targeting inflamed circulatory interface using nanocarriers - Huerta, Carlos Theodore; Zhang, Leiming; Ortiz, Yulexi Y.; Li, Yan; Zeynaloo, Elnaz; Dikici, Emre; Siahaan, Teruna J.; Deo, Sapna K.; Daunert, Sylvia; Liu, Zhao-Jun; Velazquez, Omaida C. (Frontiers in Cardiovascular Medicine, 2025)
Stem cell therapy holds significant potential for many inflammatory diseases and regenerative medicine applications. However, delivery of therapeutic cells to specific disease sites after systemic administration without indiscriminate trafficking to other non-target tissues is a major limitation of current cell therapies. Here, we describe a novel nanocarrier-directed targeted cell delivery system that enables cell surface coating with dendrimer nanocarriers containing adhesion moieties to serve as a global positioning system “GPS” to guide circulating cells to targeted lesions and mediate the anchoring of cells at the inflammation site. By exploiting cell surface ligands/receptors selectively and/or molecular moieties that are highly expressed on activated endothelium in pathologic disease states, nanocarrier-coated cells containing the counterpart binding receptors/ligands can be enabled to specifically traffic to and dock at vasculature within target lesions. We demonstrate the efficacy of the I-domain fragment of LFA-1 (idLFA-1) complexed to modified nanocarriers to facilitate the homing of mesenchymal stem cells (MSCs) to inflamed luminal endothelial cells on which ICAM-1 is highly expressed in a murine model of aortic atherosclerosis. Our method can overcome challenges imposed by the high velocity and dynamic circulatory flow of the aorta to successfully deliver MSCs to atherosclerotic regions and allow for the docking of the potentially therapeutic and immunomodulating cells. This targeted cell delivery platform can be tailored for selective systemic delivery of various types of therapeutic cells to different disease areas.